Scénario didactique : gestes d’ajustement et gestes d’étude, quelle(s) articulation(s) ? - Virginie Billon; Véronique Boiron (Éducation et Socialisation)
Our work focuses on the exploration of professional adjustment gestures within the framework of an autonomous writing workshop in kindergarten. It seeks to characterize their didactic potential with regard to the pupils’ study gestures and leads to the definition of the notion of didactic scenario.